A comparison of two motion sensors for the assessment of free-living physical activity of adolescents - Cuberek, Roman; El Ansari, Walid; Frömel, Karel; Skalik, Krzysztof; Sigmund, Erik (International journal of environmental research and public health, 2010)
This study assessed and compared the daily step counts recorded by two different motion sensors in order to estimate the free-living physical activity of 135 adolescent girls. Each girl concurrently wore a Yamax pedometer and an ActiGraph accelerometer (criterion measure) every day for seven consecutive days. The convergent validity of the pedometer can be considered intermediate when used to measure the step counts in free-living physical activity; but should be considered with caution when used to classify participants' step counts into corresponding physical activity categories because of a likelihood of 'erroneous' classification in comparison with the accelerometer.
Keywords: step counter; accelerometer; Adolescent; Motion; pohybová aktivita; Motor Activity; pedometer; pohyb těles; lidé; Female; measurement; mladiství; categorization of physical activity; monitoring; ženské pohlaví; validity; Humans